Meta Analisis Pengaruh Model Pembelajaran Project Based Learning Terhadap Kemampuan Berpikir Kreatif Matematis Siswa - Nora Susilowaty (LPPM Universitas Advent Indonesia, 2023)
Project-based learning focuses on concepts and principles, engages students in problem-solving activities and other meaningful assignments, and provides opportunities for students to independently build their own learning models so as to produce realistic student work. Project-based learning is a learning model that can improve students' mathematical creative thinking skills. The purpose of this research is to explain how the project-based learning model affects students' mathematical and creative thinking abilities as a whole and based on their educational level. The research population is a study of the effect of the project-based learning model on students' mathematical creative thinking skills that meet the publication criteria from 2012 to 2021. Coding produced 10 studies that met the criteria. Methods of data analysis using the stage of determining inclusion criteria and using effect size analysis. The results of the application of project-based learning model learning on students' mathematical creative thinking abilities as a whole have moderate effect criteria with an average effect size value of 0.73, while based on student education levels, the effect size at the Elementary School level is the largest, namely 1.14. While 0.62 for junior high school, 0.81 for high school, and 0.81 for college